Transferring the bendable substrateless GaN LED grown on a thin C-rich SiC buffer layer to flexible dielectric and metallic plates. Issue 3 (3rd January 2017) - Cheng, Chih-Hsien; Huang, Tzu-Wei; Wu, Chung-Lun; Chen, Mu Ku; Chu, Cheng Hung; Wu, Yuh-Renn; Shih, Min-Hsiung; Lee, Chao-Kuei; Kuo, Hao-Chung; Tsai, Din Ping; Lin, Gong-Ru
Abstract : The first demonstration on the bendable substrateless GaN LED on a-SiC buffer transferring to the dielectric and metallic substrates. Abstract : By growing an epitaxial GaN LED on C-rich a-SiC buffer deposited SiO2 /Si substrate, the simplified transfer to versatile flexible metallic/dielectric membranes is demonstrated. Both the high growth temperature at 1000 °C and the slow deposition rate played important roles in the meticulous MOCVD growth of n-GaN along the surface normal of the a-SiC at the very beginning. High substrate temperature facilitated the refinement of C-rich SiC buffer from amorphous to partially crystalline with (0004)-orientation, which effectively reduces the lattice mismatch between n-GaN and SiC at the interface so as to gradually improve the crystalline n-GaN regrowth. The substrateless GaN LED transferred to flexible copper plates showed reduced turn-on voltage of 2.6 V, enhanced output power of 370 mW, enlarged power-to-current slope of 1.24 W A −1, increased external quantum efficiency of 45%, and reduced efficiency droop of 15% under a bias of 300 mA. The thermal conductivity of the transferred substrate affected the EL peak wavelength shift of the substrateless GaN LED on SiC buffer. Heating the GaN LED on flexible copper plate to 65 °C only reduced its power by 10% and red-shifted its wavelength by 1 nm under a bias at 100 mA; the Auger effect resulted in a degraded EQE of 39.1% and an enlarged EQE droop of 8.5%. Bending the surface diameter of the curvature of the copper plate to 1.2 cm decayed the output power by 12% and red-shifted the EL peak by 5 nm because of the lattice strain induced quantum confined Stark effect (QCSE). Such a bendable substrateless GaN LED transferred to flexible membrane with superior heat dissipation and bending tolerance is a desired lighting element for green photonics in this era.